2006
DOI: 10.1529/biophysj.106.085191
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Through Lipid Nanotube Arrays for Structure-Function Studies of Membrane Proteins by Solid-State NMR Spectroscopy

Abstract: A novel method for studying membrane proteins in a native lipid bilayer environment by solid-state NMR spectroscopy is described and tested. Anodic aluminum oxide (AAO) substrates with flow-through 175 nm wide and 60-mum-long nanopores were employed to form macroscopically aligned peptide-containing lipid bilayers that are fluid and highly hydrated. We demonstrate that the surfaces of both leaflets of such bilayers are fully accessible to aqueous solutes. Thus, high hydration levels as well as pH and desirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Previously, it has been shown that lipid bilayers and membrane proteins can be assembled in functional conformations inside macroscopically aligned nanochannels of anodic aluminum oxide ͑AAO͒ membranes. [5][6][7][8][9][10] Recently, we have reported on subwavelength hybrid metallo-dielectric structures for the enhancement of Raman spectroscopic signals 11,12 and one might wonder whether the same applies to fluorescence signals. Others also pointed to the fluorescence enhancing properties of such platforms albeit for optical beams at normal incidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that lipid bilayers and membrane proteins can be assembled in functional conformations inside macroscopically aligned nanochannels of anodic aluminum oxide ͑AAO͒ membranes. [5][6][7][8][9][10] Recently, we have reported on subwavelength hybrid metallo-dielectric structures for the enhancement of Raman spectroscopic signals 11,12 and one might wonder whether the same applies to fluorescence signals. Others also pointed to the fluorescence enhancing properties of such platforms albeit for optical beams at normal incidence.…”
Section: Introductionmentioning
confidence: 99%
“…For the experiments we employed zwitterionic lipid bilayers that could be incorporated into nanoporous aluminum oxide membranes with minimal perturbation to the bilayer properties. [5][6][7][8][9][10] The bilayers were doped with 0.5-5.0 mol % of biotinylated lipids and exposed to 5-͑4,6-dichlorotriazinyl͒aminofluorescein ͑DTAF͒-a conjugated streptavidin-to mimic protein docking to the membrane surface. Fluorescence signals were measured as a function of the angle between the optical polarization state of the incident beams and the orientations of macroscopically ordered AAO nanochannels.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of pertinent information about integral membrane proteins can be obtained in aligned lipid bilayers [1,2]. The incorporation of a protein into an aligned lipid bilayer reveals unique structural information such as peptide tilt angle and lipid chain dynamics [3]. 2 H NMR spectroscopy of deuterated acyl chains of lipids is a powerful approach to monitor the dynamic properties inside lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Aligned bicelles are prepared by mixing long and short chain phospholipids such as DMPC and DHPC (1,2-dihexanoyl-sn-glycero-3-phosphocholine) under optimized experimental conditions [7,8]. Drawbacks to the bicelle alignment procedure include the inability to perform experiments requiring the removal or replacement of solvent after the bicelle sample is created, low sample stability of non ether-linked lipids after being heated, the inability of some lipids (such as POPC) to align in the magnetic field of the NMR spectrometer, and the limited range of alignment temperatures for a given bicelle composition [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation